Visualization Analysis of College Teaching Quality Monitoring Based on CiteSpace - Wei Li, Hao Cheng, Fang Tian, Yuzan Dai (Forest Chemicals Review, 2022)
With the progress of science and technology and the continuous advancement of teaching reform, the teaching quality of colleges and universities has become the most important issue in the reform and development of colleges and universities. This paper uses the file metrology software Citespace to study the current research situation and hot spots of teaching quality monitoring in the field of social science, through author co-occurrence analysis, research hotspot analysis, cluster analysis, research frontier analysis and other methods to sort out and explore the research object.